A constrained sub‐optimal controller for glucose regulation in type 1 diabetes mellitus. (15th February 2013) - Ghosh, Subhojit; Maka, S.
SUMMARY Patients with type 1 diabetes mellitus require exogenous insulin infusion to avoid chronic complications related to elevated glucose levels. With diabetes reaching epidemic proportions, recent times have witnessed an increased attention in the field of optimal glucose management by closed‐loop insulin delivery system. A proper glucose management scheme, in addition of maintaining the glucose level within the normal range of 80–120 mg/dL, should avoid excessive insulin delivery leading to hypoglycemia. By considering the glucose regulation as a linear quadratic problem, a constrained novel sub‐optimal controller is proposed in the present work, for the maintenance of normal glucose level in type 1 diabetic subjects. The observer free state feedback controller is based on the feedback of only physiological variables (plasma glucose and plasma insulin). Constraining the feedback elements corresponding to the non‐physiological variables avoids the use of an observer while maintaining the advantages of state feedback control. The implementation of the proposed scheme requires simple measurement protocol with no online computation. The closed‐loop performance of the controller is evaluated on a physiologically relevant model for a meal disturbance and continuous glucose infusion. Copyright © 2013 John Wiley & Sons, Ltd.